(untitled) (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2026)
Deafness is a type of disability characterized by partial or complete hearing loss in one or both ears. Deaf students in higher education face several critical challenges: (1) dependence on oral communication they cannot directly access, (2) limited sign language interpreters in regular classrooms, (3) the absence of media that converts speech into real-time text while displaying the speaker’s facial expressions. These conditions cause deaf students to struggle with following explanations, engaging in discussions, and participating actively in the learning process. However, individuals with hearing impairment tend to rely on visual learning, whereas the majority of instructional information is delivered through oral communication. This research aims to develop interactive media based on speech recognition and real-time video as a solution to improve communication in the learning process of deaf students. The novelty of this research lies in the integration of web-based speech recognition with a multi-actor interface (instructor, student, and general user) specifically designed for inclusive education in higher education settings, distinguishing it from conventional solutions. The method used is Research and Development (R&D) with the stages of needs analysis, system design, implementation, and functional testing and performance testing using Word Error Rate (WER). The overall average WER was 19.70%, with the range of WER being 14.05% (from the minimum of 13.22% to the maximum of 27.27%). The results showed that all system features performed as required, and an average WER indicated a good level of accuracy for interactive educational contexts.